The implementation and evaluation of a nutrition education programme for university elite athletes - Martinelli, L. (Progress in Nutrition, 2013)
A challenge of providing nutrition education to collegiate athletes lies in the development of an effective method for improving nutrition knowledge and attitudes. This study presents the results of a nutrition education programme, designed to improve nutrition knowledge and dietary intake in a sample of university scholarship athletes coming from different sports settings. The nutrition programme was delivered by a qualified sports nutrition professional and it consisted of six sessions targeted at improving athlete understanding of sports nutrition principles to support training, competition and health. Paired sample t-test detected a significant increase in participants’ scores for nutrition knowledge between pre- and post- intervention conditions (p<0.005). ANOVA was used to test for variation between males and females but no significant gender differences were noted. Although the nutrition education programme presented was effective in rising nutrition knowledge of the athletes, score increase did not have a significant impact on their dietary practices. Percentages of energy from macronutrients were within current dietary guidelines. The mean diet quality for both males and females was satisfactory: mean intakes of carbohydrate, protein, fat and fluid were into line with dietary recommendations. In contrast, post-test female intakes of calcium, iron, zinc, selenium and iodine were inadequate. While micronutrient intake of male participants revealed no deficiencies. This study reduces the paucity of nutrition education intervention research among university sports scholars and reveals that the nutrition education programme was effective on increasing the participants’ nutrition knowledge, but not in improving their dietary intake; these results imply that a controversial relationship links nutrition knowledge and eating patterns, suggesting new spurs for further research. Realizzazione e valutazione di un programma di educazione alimentare rivolto ad atleti universitari di livello nazionale e internazionale La principale difficoltà di un valido programma di educazione alimentare è lo sviluppo di un metodo efficace e ripetibile per migliorare lo stile alimentare dei partecipanti. Questo studio presenta i risultati di un percorso educativo finalizzato al miglioramento della conoscenza nutrizionale e delle abitudini alimentari di un gruppo di atleti universitari di alto livello, provenienti da diversi panorami sportivi. Il programma è stato condotto da dietisti qualificati e si è articolato in sei incontri inerenti i principi della nutrizione sportiva. Conoscenza nutrizionale e abitudini alimentari sono stati valutati prima e dopo l’intervento educativo, rispettivamente attraverso un questionario validato e un diario alimentare settimanale. E’ stato evidenziato un significativo incremento della conoscenza nutrizionale dei partecipanti (p<0.005) ma non un miglioramento della loro alimentazione. La qualità della dieta dei partecipanti di entrambi i sessi era soddisfacente: gli apporti medi di energia, macronutrienti e acqua rientravano negli intervalli raccomandati. Al contrario, gli apporti post-intervento di calcio, ferro, zinco, selenio e iodio delle donne erano inadeguati. Ad un aumento della conoscenza nutrizionale, dunque, non sempre consegue un miglioramento delle abitudini alimentari. I risultati ottenuti suggeriscono quindi l’esistenza di una controversa relazione tra conoscenza nutrizionale e condotta dietetica, fornendo nuovi spunti per futuri approfondimenti.